Chronic Consumer Liminality: Being Flexible in Precarious Times - Mimoun, Laetitia; Bardhi, Fleura (Journal of Consumer Research, 2022)
Abstract This study introduces the notion of chronic consumer liminality (CCL) defined as a recurrently activated state of transition experienced when engaging in frequent, multiple, and nonlinear consumer life transitions. CCL is characterized by (1) reoccurring transitions, (2) ongoing self-transformation, and (3) the embracing of precarity. We find evidence of CCL in a multimethod qualitative study of the flexible consumer lifestyle. CCL emerges as a response to the liquidification of society and the rise of a marketplace ideology of flexibility. CCL is manifested and managed through three CCL navigation processes: destabilizing consumption routines, liquidifying consumption, and asserting control over time and money. Thus, consumers experiencing CCL tend to prefer variety seeking and serendipity over routine even for mundane choices, access-based consumption across domains, and a productivity orientation toward free time. Three skills also facilitate CCL: resilient optimism, adaptability, and self-preservation. This study contributes to research on liminality, consumption in liminality, liquid consumption, and precarity. We conclude with the managerial implications of our framework.